IL13RA2-integrated genetically engineered mouse model allows for CAR T cells targeting pediatric high-grade gliomas - M. Seblani; M. Zannikou; J. T. Duffy; T. Joshi; R. N. Levine; A. Thakur; M. Puigdelloses-Vallcorba; C. M. Horbinski; J. Miska; D. Hambardzumyan; O. J. Becher; Irina V. Balyasnikova (Acta Neuropathologica Communications)
Abstract Pediatric high-grade gliomas (pHGG) and pediatric diffuse midline gliomas (pDMG) are devastating diseases without durable and curative options. Although targeted immunotherapy has shown promise, the field lacks immunocompetent animal models to study these processes in detail. To achieve this, we developed a fully immunocompetent, genetically engineered mouse model (GEMM) for pDMG and pHGG that incorporates the glioma-associated antigen, interleukin 13 receptor alpha 2 (IL13RA2). Utilizing the RCAS-Tva delivery system in Nestin-Tva mice, we induced gliomagenesis by overexpressing PDGFB and deleting p53 (p53fl/fl) or both p53 and PTEN (p53fl/fl PTENfl/fl), with or without IL13RA2 in neonatal mice. De novo tumors developed in models with and without IL13RA2, showing no statistical difference in onset (n = 33, 38 days, p = 0.62). The p53fl/fl PTENfl/fl tumors displayed more aggressive characteristics (n = 12, 31 days). Tumors exhibited features typical of high-grade glioma, including infiltration, pseudopalisading necrosis, and microvascular proliferation. They also showed a high Ki-67 index, variable IL13RA2 expression, a high frequency of CD11b + macrophages, and a low proportion of CD3 + T cells. The model proved effective for evaluating IL13RA2-targeted immunotherapies, with a significant response to CAR T-cell treatment that extended survival (46 days vs. 28 days control; p < 0.0001) and achieved 25% long-term survival in mice. This model facilitates the preclinical assessment of IL13RA2-directed therapies and holds potential for clinical application.